The integration of Artificial intelligence (AI) in literature review and its potentials to revolutionize scientific knowledge acquisition - Ilegbusi, Paul (My University, 2024)
This presentation discusses the role of artificial intelligence (AI) in enhancing the literature review process and its potential to transform scientific knowledge acquisition. The presentation highlights the importance of literature review in research and the challenges associated with the traditional manual approach. The presentation emphasizes that integrating AI in literature review can significantly improve efficiency, accuracy, and reduce bias. AI-powered tools can automate various aspects of the literature review process, including search, selection, analysis, and synthesis of relevant literature. The benefits of AI in literature review include increased efficiency, improved coverage of literature, and the ability to identify gaps in knowledge and uncover new research questions. The presentation also provides a comprehensive list of AI tools that can be used in literature review, such as Cramly.ai, Quillbot, GPT-minus 1, ChatGPT, Samwell.ai, and many others. These tools offer functionalities such as rewriting, paraphrasing, summarizing, understanding literature, and extracting key information from articles. The future of AI in literature review is promising, with emerging trends such as deep learning models and knowledge graphs. These trends have the potential to enhance the accuracy and comprehensiveness of literature reviews. In conclusion, the integration of AI in literature review has the potential to revolutionize scientific knowledge acquisition by improving efficiency, accuracy, and coverage of literature. By combining AI with human expertise, researchers can unlock new insights and accelerate scientific progress in various fields.
The integration of Artificial intelligence (AI) in literature review and its potentials to revolutionize scientific knowledge acquisition
Keywords: AI Tools; Artificial Intelligence (AI); Literature Review; Research Process; Scientific Knowledge Acquisition